Fabrication of layer-by-layer ECM/polysaccharides/electrospun composite nanofibrous scaffolds and hydrogels for in-vitro skin cell regeneration - El-Shishiny, Fatma Nabil (AUC Knowledge Fountain, 2019)
Skin burn wounds is a crucial issue that could reduce life quality. The novel tri-layered asymmetric porous scaffold has been innovated to mimic the natural skin layers. The scaffold constitutes of upper electrospun Cs-PVA layer and lower xerogel layer that made of effective skin ECM components. Both layers were stuck together by fibrin glue. The developed scaffold resulted in promising swelling capability suitable for absorbing wound exudates, followed by constant degradable weight over time which is appropriate for burn wounds environment. SEM images revealed the presence of significant pore distribution among the electrospun and xerogel layers confirmed by BET analysis. The electrospun nanofibrous layer was examined for its antibacterial property and showed expressive complete bacterial inhibition against gram-negative and gram-positive bacterial strains. Mouse embryonic fibroblast cytotoxicity and migration rate were investigated against the created asymmetrical composite. The outcome results of tissue culture experiments demonstrated significant cell proliferation and migration in presence of the constructed scaffold (P<0.0001). Complete wound closure was observed in-vitro in presence of the three scaffold asymmetrical layers against mouse embryonic fibroblast. Results of this study have been proved the superior biological characteristics of the innovated asymmetrical composite, that could further replace the burned skin layers with potential for clinical applications.